Pengembangan Metode Problem Solving dalam Mata Pelajaran Fiqih Kelas XI di MAN 9 Jombang - Muhammad Nur Latif; Mohammad Saat Ibnu Waqfin (ISLAMIKA, 2023)
In delivering material, educators still often use conventional teaching methods so that it affects the activeness and understanding of students in learning activities. It is necessary to use the right teaching method so that students can understand the material optimally. This research aims to determine the Development of Problem Solving Methods in Class IX Fiqh Subjects at MAN 9 Jombang. The method used in this research is descriptive qualitative research. Data collection techniques in this study used observation, interviews and documentation techniques. The results of this study explain that the Problem Solving Method is intentionally performing procedural tasks in a series of activities, bit by bit systematically. By using the Problem Solving Method in Fiqh subjects, it is very influential on student activity and understanding. The advantage of the Problem Solving Method is that students are trained to think in a structured and systematic way so that students know the implementation of fiqh subjects. The application of the Problem Solving Method in Fiqh subjects is limited in the capacity of students' knowledge, experience and time, this is a drawback of the Problem Solving Method.